DEPARTMENT OF TRANSPORTATION AND RELATED AGENCIES APPROPRIATIONS, FISCAL YEAR 880000 (Tufts Archival Research Center, 2007)
Senate Congressional Record for October of 1987 reporting the Senate debate concerning a smoking ban on all public transportation including airplanes, buses and trains. Stresses that in the opinion of Senator Hollings, the issue is not whether smoking is receiving enough attention, it is whether the Senate will "show some discipline." Illustrates the feelings of Senator Ford that there should be more studies concerning the effects of secondhand smoke. Concludes with the passage of the bill stating that it is unlawful to smoke on public transportation.